From the origin of NASH to the future of metabolic fatty liver disease. Issue 8 (25th February 2021) - Geier, Andreas; Tiniakos, Dina; Denk, Helmut; Trauner, Michael
Abstract : Non-alcoholic fatty liver disease (NAFLD) has become the most common cause of chronic liver disease worldwide. Understanding the pathological and molecular hallmarks from its first description to definitions of disease entities, classifications and molecular phenotypes is crucial for both appropriate clinical management and research in this complex disease. We provide an overview through almost two hundred years of clinical research from the beginnings as a nebulous disease entity of unknown origin in the 19th century to the most frequent and vigorously investigated liver disease today. The clinical discrimination between alcohol-related liver disease and NAFLD was uncommon until the 1950s and likely contributed to the late acceptance of NAFLD as a metabolic disease entity for long time. Although the term 'fatty liver hepatitis' first appeared in 1962, it was in 1980 that the term 'non-alcoholic steatohepatitis' (NASH) was coined and the histopathological hallmarks that are still valid today were defined. The 2005 NASH Clinical Research Network scoring was the first globally accepted grading and staging system for the full spectrum of NAFLD and is still used to semiquantify main histological features. In 2021, liver biopsy remains the only diagnostic procedure that can reliably assess the presence of NASH and early fibrosis but increasing efforts are made towards non-invasive testing and molecular classification of NAFLD subtypes.